Contribution of Fecal Calprotectin and Fecal Immunochemical Tests to the Evaluation of Patients with Ulcerative Colitis - Yakut, Aysun (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Yakut A. Contribution of fecal calprotectin and fecal immunochemical tests to the evaluation of patients with ulcerative colitis. Turk J Gastroenterol. 2024;35(6):509-510.